Formative evaluation of a telemedicine model for delivering clinical neurophysiology services part I: Utility, technical performance and service provider perspective - DOHERTY, COLIN (My University, 2010)
Background Formative evaluation is conducted in the early stages of system implementation to assess how it works in practice and to identify opportunities for improving technical and process performance. A formative evaluation of a teleneurophysiology service was conducted to examine its technical and sociological dimensions. Methods A teleneurophysiology service providing routine EEG investigation was established. Service use, technical performance and satisfaction of clinical neurophysiology personnel were assessed qualitatively and quantitatively. These were contrasted with a previously reported analysis of the need for teleneurophysiology, and examination of expectation and satisfaction with clinical neurophysiology services in Ireland. A preliminary cost-benefit analysis was also conducted. Results Over the course of 40 clinical sessions during 20 weeks, 142 EEG investigations were recorded and stored on a file server at a satellite centre which was 130 miles away from the host clinical neurophysiology department. Using a virtual private network, the EEGs were accessed by a consultant neurophysiologist at the host centre for interpretation. The model resulted in a 5-fold increase in access to EEG services as well as reducing average waiting times for investigation by a half. Technically the model worked well, although a temporary loss of virtual private network connectivity highlighted the need for clarity in terms of responsibility for troubleshooting and repair of equipment problems. Referral quality, communication between host and satellite centres, quality of EEG recordings, and ease of EEG review and reporting indicated that appropriate organisational processes were adopted by the service. Compared to traditional CN service delivery, the teleneurophysiology model resulted in a comparable unit cost per EEG. Conclusion Observations suggest that when traditional organisational boundaries are crossed challenges associated with the social dimension of service delivery may be amplified. Teleneurophysiology requires a governance and management that recognises its socio-technical nature.
PUBLISHED
Keywords: teleneurophysiology; teleneurophysiology